Oestrogen Rising 2016: Ireland's stained and bloodied cloths. (4th May 2017) - Harper, Catherine
ABSTRACT: A weaver, seamstress, laundress and artist, in this essay I shall spin a yarn, tangle a web, and construct a text(ile) of the inter-weave of narrative and identity that I define as my intellectual, textual, somatic and material/visual practice obsessions. My work explores 'the places in-between' in the entanglements of Irish and Northern Irish gender and identity, and in the abject fabrics of death and of desire. As an Irish feminist, sense-making of the complexities, conundrums, challenges and contradictions of my land, my cloth, my body and my culture owes much to Irish women before me who fought for female suffrage, and Irish women now – north and south of the border that divides the island of Ireland – who still struggle for equality of citizenship, social justice, human rights, and full reproductive autonomy. My contention is that when we accept that Ireland herself is a many-layered cloth, a stained and bloodied cloth, a cloth marked irreversibly by history, conflict, denial and abuse, stained by its own repression, marked through denial of all its people's rights and needs, and bloodied by its greatest export, the haemorrhage of its people, then – polemical, didactic or reflective, with more compassion, empathy, humility and heart – we just might make peace with our past.